Comparison of clinical imaging and pathological findings of various brain lesions including cerebrovascular diseases and other systemic diseases. Issue 5 (31st March 2022) - Udaka, Fukashi
Abstract : Looking back at the cases of brain cutting conducted in Sumitomo Hospital over the past 32 years, cases where clinical brain imaging could be compared with pathological findings other than degenerative diseases are examined and carefully selected, and instructive examples of them are presented. Although there are some limitations, the comparison between clinical brain imaging and pathological finding is significant to the final diagnosis and understanding of the pathogenesis of brain lesions.